Community forest enterprise markets in Mexico and Brazil: new opportunities and challenges for legal access to the forest - Molnar,A.; Gomes, D.; Sousa, R.; Vidal, N.; Hojer, R.F.; Arguelles, L.A.; Kaatz, S.; Martin, A.; Donini, G.; Scherr, Sara J.; White, A.; Kaimowitz, D. (Informa UK Limited, 2008)
A significant shift has taken place in global forest tenure, with a doubling of the forest area under community ownership (or administration over the past 15 years). There is every indication that communal tenure will double again over the next 15 years. Recognition of traditional and indigenous peoples' collective rights over forest lands has important implications for forest-rich countries—both developed and developing. Combined with dramatic changes in the structure of the forest industry and globalizing markets, this shift creates new opportunities and challenges for low-income forest producers and community enterprises to leave poverty and diversify livelihoods. The challenge for policy makers and governments is to reform outdated regulatory and incentive frameworks to support these enterprises. This article presents findings on three types of responses from communities to the new opportunities created by the tenure shift and looks specifically at community timber enterprise cases from Mexico and Brazil; recommending actions by communities, policy makers, and private sector. Changes in international and domestic forest product demand, consolidation of commodity wood sectors, new corporate responsibility commitments, and the emergence of ecosystem service markets all affect community markets. One response has been the emergence of socially-integrated, timber and non-timber based enterprises. Another has been the expansion of self-financed community conservation. A third response has been new models of collaboration between companies and communities.